If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+9=10x-11
We move all terms to the left:
5x+9-(10x-11)=0
We get rid of parentheses
5x-10x+11+9=0
We add all the numbers together, and all the variables
-5x+20=0
We move all terms containing x to the left, all other terms to the right
-5x=-20
x=-20/-5
x=+4
| Y=x/5-8 | | (2^2x+4)-9(2^x)=0 | | 9v=21+2v | | 6=0,12a^2-0,08a+0,16 | | 4x+11/9+9=3x | | 50*x=30 | | 7x+4=8x+3 | | 6w+39=13w | | 7x=(3x+20) | | 5x+7=2x+35 | | 7x+17+4x-15=90 | | 36*36+d*d=96*96 | | 3x/5+x/2=22 | | 36^2+d^2=96^2 | | 96=3(3x+8 | | 33=x/2+11 | | 7x−7=21 | | 3x+2=−49 | | 6x+29=2x-9 | | -6x-7=-106+3x | | 5x+5=-6x+115 | | 6(-4x+9)=-138 | | 13x-(3x+2)=-6-13 | | 25-19=x | | 3750=2500(1+0.25t) | | 8(w+6)=24 | | 25+15x=16x | | -7c+43c-35c-20=12 | | 5k-3=92 | | 40s-27s+19s-31s=54 | | -5d-11d+60d-5d-30d-18=-45 | | 5g^2=12g |